Analisis Pengaruh Konteks Sosial-Historis terhadap Penafsiran Ibn Kaṡīr atas QS. Al-Mā’idah [5]: 51 - Al Amin , Nazifatul Ummy; Habibie , Ilham Akbar (Contemporary Quran, 2022)
This study investigates Ibn Kaṡīr's interpretation of QS. al-Mā'idah [5]: 51, with particular emphasis on the prohibition against taking Jews and Christians as awliyā' (loyal friends or protectors). Ibn Kaṡīr  interprets awliyā' using the term muwālat, which connotes forming close friendships or alliances. This interpretation appears to contradict a hadith that he himself cites, which indicates that such relationships may be permissible under certain circumstances. The study seeks to describe and analyze how Ibn Kaṡīr's socio-historical context, particularly during the Crusades, influenced his interpretation of this verse. By employing an analytical-descriptive approach within a literature review framework, this research examines how interpretive biases can emerge when the socio-historical context of the exegete is not adequately considered. The findings reveal that Ibn Kaṡīr's stringent interpretation, which broadly prohibits Muslims from forming close alliances with Jews and Christians, is deeply rooted in the religious and political tensions of his time. The study underscores the necessity of adopting a holistic approach in Qur'anic exegesis to mitigate potential biases stemming from the socio-historical circumstances of the exegete.